Effect of 2-octylcyanoacrylate on placenta derived mesenchymal stromal cells on extracellular matrix. (November 2017) - Chen, Y. Julia; Lankford, Lee; Kabagambe, Sandra; Saenz, Zoe; Kumar, Priyadarsini; Farmer, Diana; Wang, Aijun
Abstract: Purpose: Determine the effect of 2-octylcyanoacrylate on placenta derived mesenchymal stromal cells (PMSCs) seeded onto extracellular matrix (ECM) in order to assess its biocompatibility as a potential adhesive for in-vivo fetal cell delivery. Methods: PMSCs isolated from chorionic villus tissue were seeded onto ECM. A MTS proliferation assay assessed cellular metabolic activity at various time points in PMSC-ECM with direct, indirect, and no glue contact. Conditioned media collected prior to and 24 hours after glue exposure was analyzed for secretion of human brain-derived neurotrophic factor, hepatocyte growth factor, and vascular endothelial growth factor. Results: Direct and indirect contact with 2-octylcyanoacrylate results in progressively decreased cellular metabolic activity over 24 hours compared to no glue controls. Cells with direct contact are less metabolically active than cells with indirect contact. 24 hours of glue exposure resulted in suppression of growth factor secretion that is near complete with direct contact. Discussion: Exposure to 2-octylcyanoacrylate results in decreased metabolic activity and decreased measurable secretion of growth factors by PMSCs seeded onto ECM. Thus, the application of 2-octylcyanoacrylate glue should be limited when working with cell-engineered scaffolds as its inhibitory effects on cell growth and secretory function can limit the therapeutic potential of cell-based interventions. Highlights: Cyanoacrylate glue exposure decreases metabolic activity in placenta MSCs. Cyanoacrylate glue exposure alters placenta MSCs growth factor secretion. Cyanoacrylate glue usage should be limited when working with cell based scaffolds.